An Assessment Framework for Small-Scale Coal Mining Based on Lean Thinking and Green Mining Concept - Yuliandra, Berry; Sutanto, Agus; Prasojo, Hendris (International Series on Interdisciplinary Science and Technology, 2018)
Coal mining is one of Indonesia's important industrial sectors. However, the industry is also often seen as a major cause of landscape destruction and environmental unsustainability, especially by small-scale mining. This study aims to develop an assessment framework for small-scale mining based on the concept of lean thinking and green mining. Those concept can be used to ensure that the assessment process is oriented towards good mining practices and environmental conservation efforts. Focus of the study is coal mining business located in the city of Sawahlunto. The study was conducted using descriptive method with interview as primary data collection technique. In addition to primary data, secondary data are also collected from official documents, books, and reports on mining research in the city of Sawahlunto. Validation of criteria and indicators in the assessment framework is done using Focus Group Discussion (FGD) techniques with expert teams consisting of government, mining practitioners and academics. The proposed assessment framework consists of total 10 assessment criteria with 55 indicators